2022
DOI: 10.3390/agronomy12051026
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality of Romaine Lettuce at Different Daily Light Integral in an Indoor Controlled Environment

Abstract: In this study, the effect of different photosynthetic photon flux density (PPFD) provided by LEDs (Light Emitting Diodes) and photoperiod on biomass production, morphological traits, photosynthetic performance, sensory attributes, and image texture parameters of indoor cultivated romaine lettuce was evaluated. Two cultivars of lettuce Lactuca sativa var. longifolium namely ‘Casual’ (Syngenta)—midi romaine lettuce with medium-compact heads—and ‘Elizium’ (Enza Zaden)—a mini type (Little Gem) with compact heavy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 58 publications
3
12
1
Order By: Relevance
“…Despite the expectation that HC, LDA, KNN, Log-Reg, Nai-Bay, RF, SGD, SVM, and Tree [ 12 , 31 ] would have the highest precision and accuracy, our study found otherwise. Instead, SVM, PLS, and RF algorithms showed the highest accuracy for lettuce pigment phenotyping when used with a regression model [ 20 , 36 ].…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Despite the expectation that HC, LDA, KNN, Log-Reg, Nai-Bay, RF, SGD, SVM, and Tree [ 12 , 31 ] would have the highest precision and accuracy, our study found otherwise. Instead, SVM, PLS, and RF algorithms showed the highest accuracy for lettuce pigment phenotyping when used with a regression model [ 20 , 36 ].…”
Section: Discussioncontrasting
confidence: 92%
“…Accordingly, the results showed that STEPW and VIP are useful in phenotyping plants, as reported in previous studies [ 31 , 33 , 37 ]. However, it has been noted that these methods have limitations, such as low accuracy and biases in the output.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The studied CBVF uses 91 W m − 2 LED with a PPFD of 140 μmol m − 2 s − 1 , resulting in a very low molar efficacy of 1.54 μmol J − 1 . The best performance in terms of quality and yield for lettuce production requires approximately 240 μmol m − 2 s − 1 and a 16 h photoperiod (Matysiak et al, 2022); a daily light integral (DLI) of 13.8 mol m − 2 d − 1 compared to 10.1 mol m − 2 d − 1 in the VF studied. To obtain more insight into the performance of the studied VF the yearly amount of photosynthetic active photons reaching the crops to produce a kg FW were presented in Fig.…”
Section: Comparison To Other Literaturementioning
confidence: 99%